HUBUNGAN ANTARA PENGETAHUAN SISWA TENTANG KESEHATAN REPRODUKSI DAN LOCUS OF CONTROL DENGAN PERILAKU HIDUP SEHAT - Ahmad Khoiri (Program Studi Magister Manajemen Lingkungan, 2016)
The purpose of this study was to gain an overview of the relationship between students' knowledge of reproductive health and locus of control (LOC) with a Healthy Lifestyle. Students are expected to behave menyadaari the importance of healthy living. This study uses correlational method, the sample is 120 students drawn randomly. Data were collected using the instrument in the form of grains form of statements and questions. Analysis and interpretation of data showing (1) there is a positive relationship between students 'knowledge about reproductive health with a healthy behavior, (2) there is a positive relationship between locus of control students with healthy behavior, (3) there is a positive relationship between students' knowledge about health reproduction and locus of control together with healthy behavior. The findings of this study concludes with an increase students' knowledge about reproductive health, locus of control along healthy behaviors can improve the students the importance of maintaining health